Efeito do desbaste nos parâmetros dendrométricos e na qualidade da madeira de Eucalyptus grandis W. Hill ex Maiden - Trevisan, Rômulo (2010)
This study was undertaken to evaluate the effect of thinning in the dendrometric parameters and wood quality of the Eucalyptus grandis at 18 years of age. There was analyzed a thinning experiment, located in the northern coast of Rio Grande do Sul, installed in randomized blocks with four repetitions. The seven treatments were defined according to the number of thinnings applied and ranged from zero to six interventions. The trees were selected, in each treatment, on the basis of the Assmann s dominant diameter and the central diameter of tree, being referred to as dominant and central trees, respectively. After cutting down, the trees were measured and the volume determined by the method of Smalian. Afterwards, disks were taken at the base, 25, 50, 75 and 100% of the commercial height, and at the DBH (diameter at breast height), for basic density determination. In relation to the wood fiber length, only the disk corresponding to the region of the DBH was sampled. There were selected the logs located between the DBH and 25% positions, 25% and 50%; 50% and 75%; 75% and 100% of the commercial height, for the end splits study. The results indicate that the application of thinnings caused significant gain in DBH, height and volume in central trees, without changing the form factor. For the dominant trees, the DBH and volume were modified by thinning exciding four interventions. However, with regard to the quality of lumber, more than two thinning interventions showed disadvantageous due to the excessive tree reduction and a small gain of individuals in the upper classes. The average end splits of the logs in the dominant and central trees was higher at the second log sampled, showing suggesting that sectioning should be carried in conjunction with techniques that minimize the growth stress, especially when this is performed near the half of the commercial height. The thinning did not change the pattern of axial variation of the wood basic density, and the lowest values were found near the DBH. The fiber length showed a pattern of increasing from pith to bark in all thinning intensities analyzed, independently of dominant and average stratum, and the lowest values were observed near the pith. The thinning induced variation in the logs end split, basic density and wood fiber length, both for dominant and central trees; however, there was no clear positive or negative trend, leading to the conclusion that changes in growth rate did not affect these parameters uniformly. In general, more than two thinning interventions did not result in improvements in the wood quality.